Systematic investigation of potential factors that affect the production costs of the bio-based and bio-degradable plastic polyhydroxyalkanoates (PHAs) by a costing analysis based on early process simulation - Rumjeet, Shilpa (Centre for Bioprocess Engineering Research, 2016)
A transition is needed to shift the global economy to a more sustainable and clean economy to counteract the depletion of abiotic resources, generation of emissions and waste. Replacing petroleum plastics by bio-plastics is key to this move. This study identifies the bio-based and bio-degradable plastics, polyhydroyalkanoates (PHAs) as promising alternatives to petroleum plastics. PHAs are biologically synthesised polyesters which accumulate intracellularly in the presence of excess carbon from renewable resources and, limited nutrients in the form of nitrogen, phosphorus or sulphur. Different PHA polyesters can be synthesised by varying the growth conditions of the microbial culture. The flexible nature of PHA synthesis results in a large group of PHA polyesters with a variety of properties that span those of petroleum plastics in terms of strength, rigidity, durability and mechanical properties. Due to their versatility, PHAs have a wide range of applications in packaging and coating, health care and hygiene products, fibres, adhesives, components of toner and developer fluids and medical sutures and implant materials. Waste products of PHA production are mostly carbon dioxide and water. PHAs are biodegradable in all living systems including marine environment. PHAs are also bio-compatible and thus are not toxic to living organisms. In spite of the numerous advantages that PHAs offer, they have not yet achieved substantial commercial success due to poor market penetration arising from their high costs of production. The typical PHA sale price ranged from $ 4 to 9/kg in 2014. Factors that have been reported to affect the production costs of PHAs are the PHA content and concentration achieved by the microorganism, the purification and recovery process of PHAs together with the type of carbon substrate used. Additionally, the efficiency of the cell disruption and energy required for the washing steps can also influence the production system and are addressed in this study along with the other factors. The overall PHA production system must also be sustainable minimising its energy, water usage and carbon dioxide emissions. When faced with limited time and resources, insight is needed to identify which of the aforementioned factors or combination of factors are more crucial to optimise in order to lower production costs and environmental burden. Economic assessment is a powerful tool to identify promising economically viable process options and discard unfavourable ones. Since PHA production is not an established technology, process conditions and pilot scale data are not easily available. This study proposes a generic large scale PHA production system that can be simulated using minimum inputs to deliver material and energy inventories which can further be used to investigate the production costs of PHAs. The PHA monomer that was simulated is the most characterised PHA, polyhydroxybutyrate (PHB).